The Influence of Learning Styles (Visual, Kinesthetic and Auditory) on the Independence of Elementary Students’ Learning - Muhammad Mujtaba Mitra Zuana; Sumarni Rumfot; Firman Aziz; Eka Selvi Handayani; Nana Citrawati Lestari (Journal on Education, 2023)
The purpose of this research is to explain the effect of visual, auditory, and kinesthetic learning styles on the learning independence of elementary school students in one of the public schools in Jakarta. This research is a quantitative research with linear regression research method. Quantitative research according to Sugiyono can be interpreted as a research method based on the philosophy of positivism, used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical in nature with the aim of testing hypotheses which has been set. In this study using the linear regression method, namely statistical techniques to create a model and investigate the effect of one or several independent variables on one response variable. Based on the results of the research, data analysis, and discussion that was carried out in the previous chapter, it can be concluded from 112 respondents that students with dominant visual learning styles are 56 students, auditory learning styles are 21 students, kinesthetic learning styles are 13 students, visual learning styles and auditory as many as 10 students, visual and kinesthetic learning styles as many as 6 students, auditory and kinesthetic learning styles as many as 4 students, and students with the three dominant learning styles as many as 2 students